Atributos físicos e químicos de um argissolo com pastagem (Panicum maximum Jacq. : /PR - 86 Milênio) adubada com diferentes doses de nitrogênio - Costa, Marco Aurélio Teixeira (2012)
Increasing productivity in livestock systems have been increasingly necessary in view of the growing demand for animal products. The intensification of grazing allows increasing animal productivity by explored area. The sustainability of this production system depends on use of appropriate techniques for management of the soil-plant-animal system. The increase in stocking rates is associated with soil compaction. This study aimed to evaluate, in long-term experiment, the effect of intensification of grazing on physical and chemical of soil and the technical sustainability of the cattle production system of rotational grazing with constant grazing pressure. The intensification of grazing was based on increasing the productivity of the pasture by the use of increasing nitrogen rates and adjust stocking rate as a function of pasture production increased at each level evaluated. There wasn?t restriction to root growth when soil resistance to penetration was less than 1 MPa. The trampling of the animals reduced the total soil porosity in the layer of 0 to 0.10 m. A reduction in soil porosity was due to loss of pore diameter between 0.003 and 0.03 mm. The use of pasture for a long period with proper grazing pressure has allowed soil carbon accumulation. The higher intensification of grazing was the largest rate of soil carbon accumulation. Treatments most intensified had the highest amount of carbon stored after fourteen years of pasture implementation. The results showed that the intensification of grazing compacted soil in the area of animal trampling, but the level of compaction did not affect the pasture productivity. The grazing intensification increased the water retention capacity,soil carbon storage and cation exchange capacity, increasing the productive capacity of the soil evaluated.